Wine globalization : a new comparative history - Anderson, Kym; Pinilla, Vicente, 1959- (Cambridge : Cambridge University Press, 2018)
In this anthology, editors Kym Anderson and Vicente Pinilla have gathered together some of the world's leading wine economists and economic historians to examine the development of national wine industries before and during the two waves of globalization. The empirically-based chapters analyse developments in all key wine-producing and consuming countries using a common methodology to explain long-term trends and cycles in wine production, consumption, and trade. The authors cover topics such as the role of new technologies, policies, institutions, as well as exchange rate movements, international market developments, evolutions in grape varieties, and wine quality changes. The final chapter draws on an economic model of global wine markets, to project those markets to 2025 based on various assumptions about population and income growth, real exchange rates, and other factors. All authors of the book contributed to a unique global database of annual data back to the mid-nineteenth century which has been compiled by the book editors.
Title from publisher's bibliographic system (viewed on 12 Feb 2018).
Keywords: Wine industry; International trade